1999
DOI: 10.1007/s004150050435
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of central pontine and extrapontine myelinolysis ( n = 44)

Abstract: The findings in 44 patients (42 of whom were chronic alcoholics) with central pontine myelinolysis show that the outcome does not depend on the severity of neurological deficits during the acute phase of the condition or on concomitant internal diseases, including the degree of hyponatremia. Of the 34 patients for whom follow-up data were available, 32 survived. Of these 11 completely recovered, 11 had some deficits but were independent, and 10 were dependent (4 through disorders of memory or cognition, 3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
142
2
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 21 publications
12
142
2
8
Order By: Relevance
“…Although a prior study mentioned a similar clinicoradiologic disconnect (based on a single patient whose MRI results did not change despite clinical improvement), 7 previous studies have not attempted to correlate severe radiologic abnormalities on MRI with clinical outcome. A persistently abnormal MRI signal after clinical improvement in CPM has been previously appreciated and has been attributed to residual gliosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a prior study mentioned a similar clinicoradiologic disconnect (based on a single patient whose MRI results did not change despite clinical improvement), 7 previous studies have not attempted to correlate severe radiologic abnormalities on MRI with clinical outcome. A persistently abnormal MRI signal after clinical improvement in CPM has been previously appreciated and has been attributed to residual gliosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study reported no correlation between the size of the pontine lesion on brain magnetic resonance imaging (MRI) and clinical course; however, besides a single case description, no details or data were provided to support this conclusion. 7 Therefore, we performed this study to evaluate whether any clinical or laboratory data could predict functional outcome in patients with CPM, with special interest in determining whether more extensive pontine T2 signal abnormality was an indicator of poor outcome in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions associated with osmotic myelinolysis include alcoholism, alcohol withdrawal, malnutrition, liver transplantation, cirrhosis and severe burns [95]. Prognosis is quite variable, with approximately one-third of patients recovering completely, onethird having mild residual neurologic deficits and one-third remaining severely neurologically impaired [96].…”
Section: Osmotic Myelinolysismentioning
confidence: 99%
“…Over the course of weeks, the diffusion abnormalities may completely resolve or demonstrate T 2 shine-through [95,98,99]. Resolution of diffusion abnormalities may predict a better prognosis for the patient [99], although this is controversial [96].…”
Section: Osmotic Myelinolysismentioning
confidence: 99%